Socio-Economic Conditions of Fishermen Population: With Special Reference to Chombala Harbour, Kerala - Jasna P. T. AND Sanghamitra Palai
Background/Objectives: the specific objectives of the study are (1) to examine the socio-economic conditions of the fishermen community in the study area. (2) To investigate the problems faced by fishermen. (3) To suggest suitable policy measures to improve the conditions of fishermen society Methods/Statistical analysis: The study is based on primary data and secondary data. The primary data were collected through a structured schedule and samples are drawn by employing simple random sampling method. Findings: The Chombala fisheries area is a developed fishing sector. Both mechanized and motorized fishing sectors have people of good socio-economic condition. By analyzing the both the categories, it shows that the mechanized category has better improvement than motorized category. Improvements/Applications: During the ban period, an alternative employment opportunity may be provided to the fishermen. To create more infrastructural facilities for storing and freezing of fish catch. Exporting of fish directly from Chombala, and uninterrupted fuel distribution at cheaper rate are the need of the hour for Chombala fishing community.